Spf1 and Ste24: quality controllers of transmembrane protein topology in the eukaryotic cell - Tipper, Donald J.; Harley, Carol A. (Frontiers in Cell and Developmental Biology, 2023)
DNA replication, transcription and translation in eukaryotic cells occur with decreasing but still high fidelity. In contrast, for the estimated 33% of the human proteome that is inserted as transmembrane (TM) proteins, insertion with non-functional structure or topology is frequent.Correct topology is essential for function and trafficking to appropriate cellular compartments and is controlled principally by responses to charged residues within 15 residues of the inserted TM domain (TMD); the flank with the higher positive charge remains in the cytosol (inside), following the Positive Inside Rule (PIR). Yeast (Saccharomyces cerevisiae) mutants that increase insertion contrary to the PIR were selected (Tipper and Harley, 2002). Mutants with strong phenotypes were found only in SPF1 and STE24 (human cell orthologs are ATP13A1 and ZMPSte24) with, at the time, no known relevant functions. Spf1/Atp13A1 is now known to dislocate to the cytosol TM proteins inserted contrary to the PIR, allowing energy-conserving reinsertion. We hypothesize that Spf1 and Ste24 both recognizes the short, positively charged ER luminal peptides of TM proteins inserted contrary to the PIR, accepting these peptides into their large membrane-spanning, waterfilled cavities through interaction with their many interior surface negative charges. While entry was demonstrated for Spf1 (McKenna et al., 2020(McKenna et al., , 2022)), no published evidence directly demonstrates substrate entry to the Ste24 cavity, internal access to its zinc metalloprotease (ZMP) site or active withdrawal of fragments, which may be essential for function. Spf1 and Ste24 comprise a PIR quality control system, conserved in all eukaryotes, presumably evolved in prokaryotic progenitors as they gained differentiated membrane functions. About 75% of the PIR is imposed by this quality control system which joins the UPR, ERAD and autophagy (ER-phagy) in coordinated, overlapping quality control of ER protein function.